2012
DOI: 10.1111/j.1365-2125.2012.04259.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of adult age on the total and free clearance and protein binding of (R)‐ and (S)‐warfarin

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT• Hepatic drug clearance is thought to be reduced with age. However for highly protein bound drugs, which are cleared by capacity-limited metabolism, studies on total clearance have been conflicting. The hypothesis that protein binding decreases with age has been used to explain this.• Warfarin is a highly protein bound drug, which is cleared by capacity-limited metabolism. There are conflicting or little data on the relationship between adult age and total and free clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 22 publications
3
22
0
Order By: Relevance
“…The decrease in CL PT shown here (39%) is consistent with lower recovery of 4‐hydroxymephenytoin (35%) and a decreased S : R enantiomeric ratio (25%) in the urine of patients ≥50 years , although the effect of changes in renal function may contribute to this result. In the eight studies that report changes in total S‐warfarin clearance with ageing, most found a significant decrease with age, although in two of the studies this was only a trend . The majority of these studies were not designed to investigate specifically changes in clearance with age and data are not available to allow for a direct comparison with the Simcyp® data generated here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease in CL PT shown here (39%) is consistent with lower recovery of 4‐hydroxymephenytoin (35%) and a decreased S : R enantiomeric ratio (25%) in the urine of patients ≥50 years , although the effect of changes in renal function may contribute to this result. In the eight studies that report changes in total S‐warfarin clearance with ageing, most found a significant decrease with age, although in two of the studies this was only a trend . The majority of these studies were not designed to investigate specifically changes in clearance with age and data are not available to allow for a direct comparison with the Simcyp® data generated here.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of these studies were not designed to investigate specifically changes in clearance with age and data are not available to allow for a direct comparison with the Simcyp® data generated here. However, for the studies in which multiple regression analysis or population pharmacokinetic modelling was used on populations of 39–306 patients, the decline in S‐warfarin clearance with age was reported to be 0.3‐1% per year , which roughly translates to a 14–45% decline between the young and elderly age groups used in the Simcyp® simulations. For one recent study that specifically investigated the influence of adult age on warfarin clearances , it was possible to stratify the results as shown in Table .…”
Section: Discussionmentioning
confidence: 99%
“…Thus older patients are more sensitive to warfarin compared with younger patients. Age‐related changes in drug response are multifactorial with a decline in clearance, albumin binding, or renal excretion contributing to pharmacokinetic changes . Moreover, the increase in comorbid conditions and concomitant medication use in the elderly may influence warfarin response in complex ways through drug‐drug and drug‐disease interactions.…”
Section: Discussionmentioning
confidence: 99%
“…However, Jensen et al (27) have previously demonstrated that the TTA time increases with age. The metabolic clearance rate of warfarin would decrease, whereas its protein-binding rate would not increase; thus, Jensen et al (27) considered that age may affect an individual's sensitivity to warfarin and first TTA time. Therefore, further studies are required to investigate this phenomenon.…”
Section: Initial Dosage (Mg) Heart Failure Liver Function -----------mentioning
confidence: 99%